Perancangan Sistem Informasi Penjualan Tunai Pada Toko Asf Sport Gear - Budiarto, Eko (Jurnal SIGMA, 2023)
ASF Sport Gear Shop is a sports equipment shop that sells various sports equipment, and sports accessories for women or men sports equipment that includes several categories including t-shirts, jersey, soccer jackets, soccer shoes, futsal shoes, running shoes, sneakers , and hat. Asf Sport Gear is one of the stores whose buying and selling process still uses a manual system. In the process of selling goods, it is usually still written in sales books or notes only. In the process of knowing the stock of goods in the warehouse also must check one by one. Therefore, an information system is made for ASF Sport Gear. The system is made in order to help speed up the work completion process. In the sales process, making the memorandum is automatic, so it does not need to be written in the book. Checking stock of goods can be known quickly without having to check one by one. Thus the system can improve the performance of ASF Sport Gear. This research provides a solution to the problem for the store, as one of the fields of business that is needed by the use of computer methods as a means of transaction activities.. Keywords: System, Information, Sales, Cash, Web